Imprinted genes as potential genetic and epigenetic toxicologic targets. - Murphy, S K (2000)
Genomic imprinting is an epigenetic phenomenon in eutherian mammals that results in the differential expression of the paternally and maternally inherited alleles of a gene. Imprinted genes are necessary for normal mammalian development. This requirement has been proposed to have evolved because of an interparental genetic battle for the utilization of maternal resources during gestation and postnatally. The nonrandom requisite for monoallelic expression of a subset of genes has also resulted in the formation of susceptibility loci for neurobehavioral disorders, developmental disorders, and cancer. Since imprinting involves both cytosine methylation within CpG islands and changes in chromatin structure, imprinted genes are potential targets for dysregulation by epigenetic toxicants that modify DNA methylation and histone acetylation.